Factors affecting disclosure practices of annual report zakat institutions in Malaysia - Sapingi, Raedah; Puat Nelson, Sherliza; Sheikh Obid, Siti Normala (2017)
As the agent to the government in collecting and disbursing zakat money, zakat institutions are accountable to inform the public on how they managed the money i.e. via disclosure of zakat information in the annual report. Nevertheless, zakat institutions that supposed to disclose their activities have been argued to have low disclosure levels, it is compounded with comments from public that demand more details information especially on zakat disbursement activities. Hence, this paper interested to explore the reasons behind all these. To have better understanding the scenario, hence semi-structured interview with zakat payers, zakat officers and zakat recipients were conducted. The zakat payer category was further divided into 2 i.e. corporate zakat payers and individual zakat payers, while zakat officers and zakat recipients were selected from 3 states that represent 3 different organizational structure of zakat institutions. The findings revealed factors such as the issue of accessibility and availability, the status or organizational structure of zakat institutions and some vital issues related to the staff of zakat institutions have been raised by the participants. As a conclusion, the zakat institutions have tried their best in providing the zakat information to the public, despite that they are also facing many internal issues that probably difficult for the public to understand coupled with some areas that the public also fail to notice.